Factors Becoming The Students’ Problems in Learning English-2 As Seen on Their Sentences: (A Diagnostic Research on Semester-2 Students of Business Faculty, Buddhi Dharma University, Academic Year of 2017 - 2018) - PC. Sudarmadi (e-LinguaTera, 2021)
Learning foreign language, specifically English langauge as the international language, may make some students feel bored. The feelings emerge because of some factors experienced by the students. The factors are lack of interest to learn it, lack of basic knowledge of it, or lack of motivation to learn it. All of the factors reasoning may be caused by the late to build and have motivation to learn the langauge. For students of higher education institutions, the students have to have enough basic knowledge of the language learned because actually the students have learned the language since they were in high schools. Even, some students might have learnt English language since when they were in junior high schools. The basic knowledge can actualy give very dominant influence on their learning continuity. Many students taking English-2, in Faculty of Business, Buddhi Dharma University, seem to feel the significance of having basic knowledge in order that they could improve their English mastery. Therefore, those who don’t have enough basic knowledge got some problem to improve their English. Meanwhile those who have got enough basic knowledge could continue improve their skills in the use of the English language. Relating to the learning activities, Edgar Dale (1962) stated that there are two kinds of learning; they are passive learning and active learning. The best way to improve the learning must be about activating the both, active and passive learning. However, to activate the both is not a simple thing. There are some factors that the general students face like the students of Semester-2, Business Faculty have faced. The factors that make problems are the motivation to learn, the opportunity to practice, the lack of basic knowledge, etc. Some students may have good enough basic knowledge, while some other students may have not enough basic knowledge to improve their skills. Indeed, problems can disrupt the students to improve their capability to learn English as a foreign language. This condition creates another problem for the teachers to improve the class activity as it should be